Synthesis and characterization of hemicellulose-based polymeric gel film from tea leaf brewing waste - Taşar, Şeyda; Özer, Ahmet (CI and CEQ, 2021)
In this study, hemicellulose-based polymeric gel films were synthesized using the free radical polymerization mechanism. Hemicellulose was obtained from tea leaf brewing waste by using delignification process. Polymeric gel films were produced in accordance with solution-casting technique. The effects of synthesis parameters were investigated on the structure and properties of gel films. For this purpose, the hemicellulose-based synthesized gel films were characterized by analytical test. Experimental results indicated that hemicellulose-based gel films absorbed moisture at the rate of maximum 1% in 100% relative humidity environment. The lowest water vapor permeability (WVP) value was measured to be 5.88×10-10 g/(s Pa m), for the hemicellulose-based film including chitosan. The average solubility values of the produced polymeric films varied between approximately 0.4 and 1.8%. It was observed that the optical transparency of hemicellulose-based polymeric gel films changed from about 45 to 65% and the opacity/thickness values were from 0.0027 to 0.0011 ?m-1. As a result, it was found that the physicochemical and morphological properties of the synthesized films are greatly influenced by the composition of the films. © 2021, CI and CEQ. All rights reserved.
Sinteza i karakterizacija polimernog gel-filma na bazi hemikeluloze iz otpada digestije liš?a ?aja
Keywords: Biodegradable; Characterization; Gel film; Hemicellulose; Polymer